Empirical evidence of the gender pay gap in NZ - Gail Pacheco; Chao Li; Bill Cochrane (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2017)
Using recent data, and a variety of econometric techniques, this study examines the gender pay gap in New Zealand (NZ). The need for this study arises as the information that is regularly cited on the pay gap (based on average or median earnings for males and females) does not control for differences in individual, household, occupation, industry or other job characteristics, and there has been a lack of robust analysis in NZ, based on data post-2003.
Keywords: 330